GAJI SEBAGAI VARIABEL PEMODERASI PADA PENGARUH WORKPLACE OSCTRACISM DAN WORKPLACE HARASSMENT TERHADAP EMPLOYEE LIFE SATISFACTION - Larasati, Nike; Ahsani, Riska Fii; Murningsih, Setia (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.10.TAHUN.2024, 2024)
Workers spend 40 hours a week or more of their lives at work. It can be said that employees communicate more with their coworkers than with their loved ones. And sometimes, this relationship can turn into a true friendship, when employees find the right balance between personal and professional, friendship in the workplace can increase employee happiness, engagement, and work-life satisfaction. However, in organizational practices there are still many forms of violence that occur within the organization. Workplace violence in this study is emphasized in the form of workplace ostracism and workplace harassment which can have a negative effect on employee work-life satisfaction. This study examines the effect of workplace ostracism and workplace harassment on employee life satisfaction moderated by salary. The sample in this study was 140 female employees from Central Java and DIY. The results show that workplace ostracism does not have a negative effect on employee life satisfaction in female employees in Central Java and DIY, while workplace harassment has a negative and significant effect on employee life satisfaction in female employees in Central Java and DIY. For salary cannot moderate the influence of workplace ostracism and workplace harassment on employee life satisfaction. The software used to process data in this study is SPSS with multiple regression analysis.